Arthroscopic Osteosynthesis for the Treatment of Coronoid Process Fractures: A Case Series - Noriaki Shimada; Katsuhiko ShirakiIt; Kazuo Saita (Case Reports in Orthopedics)
The treatment strategy and surgical indication for coronoid process fractures are not clear. Many methods of surgery have been described. We report on the use of arthroscopic osteosynthesis for this type of fracture. This method is minimally invasive and effective for confirming the reduction, and it is advantageous for postoperative pain and early recovery after surgery.